2022
DOI: 10.1111/jvim.16535
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral biomarkers of oxidative stress in dogs with acute pancreatitis

Abstract: Background Oxidative stress is considered a pathomechanism of acute pancreatitis (AP), but no studies have extensively characterized oxidant status in dogs with naturally‐occurring AP. Hypothesis or Objectives Evaluate measures of oxidant status in dogs with AP and explore whether these measures correlate with AP severity. Animals Fifteen dogs with AP and 9 control dogs. Methods Prospective, controlled observational study. Plasma reactive metabolite (RM) concentrations, antioxidant potential (AOP), and urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Therefore, it may be useful as an indicator in cases in which rapid therapeutic intervention must be assessed. Recent human and veterinary medicine studies have revealed that evaluating both positive APPs and negative APPs in patients may be better for confirming the degree of inflammation and predicting survival (11,27,40,41). For instance, during inflammation, the plasma CRP concentration increases, while the PAB concentration decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be useful as an indicator in cases in which rapid therapeutic intervention must be assessed. Recent human and veterinary medicine studies have revealed that evaluating both positive APPs and negative APPs in patients may be better for confirming the degree of inflammation and predicting survival (11,27,40,41). For instance, during inflammation, the plasma CRP concentration increases, while the PAB concentration decreases.…”
Section: Discussionmentioning
confidence: 99%